2014
DOI: 10.1556/jba.3.2014.018
|View full text |Cite
|
Sign up to set email alerts
|

How the economic situation moderates the influence of available money on compulsive buying of students — a comparative study between Turkey and Greece

Abstract: Background and aims: Few studies about compulsive buying consider the economic framing situation. This study is concerned with the impact of different economic environments - the crisis in Greece vs. the boom in Turkey - on compulsive buying tendencies of students, while taking the role of gender and available money into account. Methods: Compulsive buying was measured by a Greek and Turkish translation of the German Compulsive Buying Scale (Raab, Neuner, Reisch & Scherhorn, 2005) in Greece and Turkey, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Ergin (2010) also explained the same findings in Turkish society. However, several research findings such as (O'Guinn and Faber, 1989; Scherhorn et al , 1990; Mueller et al , 2011; Unger, et al , 2014; Leite and Silva, 2015) showed that income does not have a significant relationship to purchasing behavior compulsive. The inconsistency of the research findings indeed becomes an important issue, because humans as compulsive buying decision-makers apparently are motivated by psychological factors, as in the findings of Kellet and Bolton (2009) and Claes et al (2010), which showed that compulsive buying has negative reinforcing properties and is used to escape negative feelings such as anxiety, depression, tension, or boredom.…”
Section: Introductionmentioning
confidence: 98%
“…Ergin (2010) also explained the same findings in Turkish society. However, several research findings such as (O'Guinn and Faber, 1989; Scherhorn et al , 1990; Mueller et al , 2011; Unger, et al , 2014; Leite and Silva, 2015) showed that income does not have a significant relationship to purchasing behavior compulsive. The inconsistency of the research findings indeed becomes an important issue, because humans as compulsive buying decision-makers apparently are motivated by psychological factors, as in the findings of Kellet and Bolton (2009) and Claes et al (2010), which showed that compulsive buying has negative reinforcing properties and is used to escape negative feelings such as anxiety, depression, tension, or boredom.…”
Section: Introductionmentioning
confidence: 98%
“…However, the presently available neurological evidence does not fully explain how concrete neural mechanisms and cognitive processes can cause normal-shopping behavior to become addictive in the absence of exogenous drug stimulation (Clark, 2014 ; Engel and Caceda, 2015 ). Unlike in other addictive conditions, it has been stated that the development of CBB depends on the presence of particular cultural mechanisms, such as a market-based economy, a wide variety of available goods, disposable income, and materialistic values (Unger et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional perception in the store is classified into two dimensions, namely positive emotion (positive emotion) and negative emotion (negative emotion) (Unger et al, 2014). Positive emotions can be created through consumer responses to in-store stimuli.…”
Section: Positive Emotionmentioning
confidence: 99%
“…Money available is a condition where consumers have funds or convenience in conducting transactions (Beatty & Ferrell, 1998). Consumers with income or ease of transaction will have the freedom to make purchases so that if the consumer is affected by the stimulus in the outlet, the consumer can be encouraged to do impulse buying (Unger, Papastamatelou, Okan, & Aytas, 2014). Finally, some factors are expected to further encourage impulse buying, namely positive emotion.…”
Section: Introductionmentioning
confidence: 99%